2016
DOI: 10.15226/sojmid/4/3/00156
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Root-Nodule Bacteria Isolated from Hedysarum spinosissimum L, Growing in Mining Sites of Northeastern Region of Morocco

Abstract: expensive and harmful to soil integrity and microbial diversity [3,4]. Phytoremediation appears as a good alternative as plants can indeed bio-concentrate (phytoextraction) as well as bio-immobilize (phytostabilization) toxic metals through in situ rhizospheric processes [1,2]. However, mining sites in semi-arid areas are characterized by low vegetation cover due to the unfavorable effects of a combination of environmental factors, including metals toxicity, nutrient deficiency, poor soil structure and low wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Although Bacillus has not been described as legume symbiont, several Bacillus strains have been identified as endophytic bacteria. They have been isolated from a variety of plants, including legume plants as Medicago polymorPha (Chinnaswamy et al, 2018), Dalbergia odorifera (Lu et al, 2017), Glycine max (Hong et al, 2007), Cajanus cajan (Rajendran et al, 2007) , Hedysarum spinosissimum (Sbabou et al, 2016) and Prosopis species. Bacteria belonging to genus Bacillus have been isolated from the endosphere and rhizosphere of Prosopis juliflora (Khan et al, 2014; Abdelmoteleb et al, 2017) and Prosopis farcta nodules (Fterich et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although Bacillus has not been described as legume symbiont, several Bacillus strains have been identified as endophytic bacteria. They have been isolated from a variety of plants, including legume plants as Medicago polymorPha (Chinnaswamy et al, 2018), Dalbergia odorifera (Lu et al, 2017), Glycine max (Hong et al, 2007), Cajanus cajan (Rajendran et al, 2007) , Hedysarum spinosissimum (Sbabou et al, 2016) and Prosopis species. Bacteria belonging to genus Bacillus have been isolated from the endosphere and rhizosphere of Prosopis juliflora (Khan et al, 2014; Abdelmoteleb et al, 2017) and Prosopis farcta nodules (Fterich et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These same limitations can also be found in the work of Sbabou et al . (), who described species of the three subclasses (α, β and γ‐proteobacteria) present in Hedysarum nodules. From that data it can be inferred only that the bacteria are endophytic to the nodules, but not necessarily that they have the capacity to form the nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study conducted with Bradyrhizobium strain isolated from greengram nodules (Vigna radiata), showed similar results with a decrease of the concentration of nickel and zinc in plant organs and plant growth promoting activities. Sbabou et al, 2016 isolated two bacteria from the nodules of the legume Hedysarum spinosissimum growing in metal contaminated soils in Morocco and showed that their inoculation promoted host plant growth and suppressed Zn toxicity symptoms in plants, enhancing their phytostabilization potential.…”
Section: Remediation Of Mine Tailings Using Phytostabilizationmentioning
confidence: 99%